FORMULATION DRINK HEALTH MATERIAL BASE OF BUTTERFLY PEA FLOWER (Clitoria ternatea L.) AND BUSINESS DESIGN INNOVATION - Tarra Syabriena; Esti Mumpuni; Esti Mulatsari (Edusaintek)
The COVID-19 pandemic has increased the use of herbal supplements, creating opportunities for developing butterfly pea flower (Clitoria ternatea L.) as a health beverage. This study aimed to formulate a stable, preferred product and design its business scheme. Four formulations with 2 grams of butterfly pea flower, varying amounts of mint leaves (0.8 g or 0.5 g) and lemon (0.35 g or 0.5 g) were tested. A hedonic test with 20 semi-trained panelists determined the most preferred formula. The selected formula underwent moisture content analysis using the thermogravimetric method at 105°C. Shelf life was evaluated with the ASLT Arrhenius model at 25°C, 35°C, and 45°C over 20 days, assessing moisture content, organoleptic properties, and pH. Microbial contamination, including Total Plate Count (ALT) and Yeast and Mold Count (AKK), as well as heavy metal levels (As, Hg, Cd, Pb) using AAS, were also examined. Results showed Formula 2 as the most preferred, with 8.13% moisture content and a shelf life of 6.9 months at 25°C in sealed packaging. Aroma was the most affected parameter during storage. Microbial analysis recorded ALT at 3×10³ CFU/g and AKK at 5×10² CFU/g. Heavy metal content met BPOM and SNI standards. Thus, Formula 2 was identified as the best formulation for commercial development.